Analisis Strategi Pengembangan Industri Coklat Lokal COSIK Berbasis Kakao Kabupaten Sikka - Anastasia Krisyanti; Emilianus Eo Kutu Goo; Patricius Santio L.S.Botu; Maria Fitriana Dewi Damayanti; Maria Rosadalima; Mikhael Anjelo (Jurnal Pelayanan Masyarakat, 2025)
This study aims to describe the production process, business strategy, and product offerings of the COSIK chocolate factory located in Maumere, Sikka Regency, East Nusa Tenggara. The COSIK chocolate factory utilizes local raw materials, such as cocoa beans, obtained directly from local farmers, and implements a processing process without the use of chemical preservatives. This approach not only increases the added value of local products but also supports community economic empowerment through partnerships with cocoa farmers in the region. Furthermore, the use of simple yet modern technology enables a hygienic production process that meets quality standards. The results show that the COSIK chocolate factory contributes to improving the quality of local cocoa, developing innovative products based on natural ingredients, and strengthening the region's identity as a producer of quality chocolate. Thus, COSIK serves not only as a production unit but also as a sustainable business model that integrates environmental, social, and economic aspects in a food processing industry based on local resources.